Efficacy of Intra-vitreal Bevacizumab for Resolution of Macular Edema Secondary to Central Retinal Vein Occlusion - Afshan Ali, Muhammad Younis Tahir (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the efficacy of intravitreal injection of Bevacizumab in resolution of macular edema in patients of central retinal vein occlusion. Material and Methods: It was a descriptive case series, conducted at Institute of Ophthalmology unit III, Mayo Hospital Lahore and Bahawal – Victoria Hospital Bahawalpur simultaneously. A total of 60 cases were selected though purposive sampling for this study. Diagnosis was ascertained on fundus fluorescein angiography. Pre and post injection macular edema was measured on optical coherence tomography on the day of drug administration and thirty days after it. Results: Mean macular thickness before treatment was 663.10 ± 109.76 microns and after treatment mean thickness was 453.06 ± 106.09 microns which was a significant (p = 0.0000001) finding. Majority (75%) of patients achieved a reduction of ? 200 microns in their retinal thickness after treatment. Whereas in the remaining 15 (25%) patients reduction in retinal thickness was < 200 microns. These findings were independent of gender bias. Conclusion: Intravitreal injection of Bevacizumab is effective in the resolution of macular edema in the patients of central retinal vein occlusion. Key words: Central retinal vein occlusion, macular edema, Bevacizumab.